Epidemiological scenarios for human rabies exposure notified in Colombia during ten years: A challenge to implement surveillance actions with a differential approach on vulnerable populations. - Marcela Rocío Arias Caicedo; Diego de Arruda Xavier; Catalina Alejandra Arias Caicedo; Etiene Andrade; Isis Abel (PLoS ONE)
Based on notified cases of human rabies exposure and human deaths by rabies to Colombia public health surveillance system between 2007 and 2016, we conducted a spatiotemporal analysis to identify epidemiological scenarios of high human rabies exposure due to dogs, cats, bats, or farm animals (n = 666,411 cases). The incidence rate of human rabies exposures was analyzed by using geographical information system (spatiotemporal distribution and Cluster and Outlier Analysis (Anselin Local Moran's I)) data for all Colombian cities. The incidence rate of human rabies exposures due to dogs and cats showed an increasing trend, while aggression due bats and farm animals fluctuated throughout the analyzed period. Human deaths by rabies transmitted by cat and bat occurred in the Andean and Orinoquia regions, which had urban and rural scenarios. The urban scenario showed the highest exposure to human rabies due to cats and dogs in cities characterized with high human population density and greater economic development. In contrary, the highest human rabies exposure in the rural scenario was observed due to contact of mucosa or injured skin with the infected saliva of farm animals with the rabies virus, principally among workers in the agroforestry area. The inequality scenario showed some outlier cities with high human rabies exposure due to farm animals principally in the Pacific region (characterized by the highest poverty rates in Colombia), being Afro-descendant and indigenous population the most exposed. The highest exposure due to bats bite was observed among indigenous people residing in cities of the Amazon region as a dispersed population (Amazonian scenario). None of the high exposure scenarios were related to human deaths by rabies due to dogs aggression. The identified scenarios can help develop better surveillance systems with a differential approach to the vulnerable population and strengthening them in areas with rabies viral circulation.